Update on Blastocystis: highlights from the Fourth International Blastocystis Conference [version 1; peer review: 2 approved] - Ana M. Figueiredo; Varol Tunali; Daisy Shaw; David Carmena; Anastasios D. Tsaousis; Eleni Gentekaki (Open Research Europe)
While the stramenopile Blastocystis, first discovered in 1911, is considered the most prevalent enteric protist in humans, its biology remains largely unexplored. Clinical studies have only recently begun investigating the role of Blastocystis in the gut and its relationship with the gut microbiome, and whether it plays a pathogenic role in human and animal health. Aiming to gather leading researchers in the field to encourage and stimulate cross-disciplinary dialogue while fostering long-term international collaborations, the Fourth International Blastocystis Conference was hosted from the 17th to the 19th of September 2024 in Heraklion (Crete, Greece). The event was mainly supported by the COST Action CA21105, “Blastocystis under One Health”, and the Microbiology Society. The multi- and interdisciplinary conference programme covered all aspects related to Blastocystis evolutionary biology and advances in omics, intestinal ecology (gut microbiome), clinical significance and association with disease, diagnosis and molecular characterisation, as well as epidemiology and One Health. The high-quality presentations discussed at the conference provided researchers with a synthesis of recent advancements, while key research questions, knowledge gaps, and future steps in Blastocystis research were identified. Herein, we aim to provide a thorough overview of the presentations at the congress. The COST Action CA21105, 'Blastocystis under One Health,' will build on the insights and collaborations fostered during the conference, promoting integrative research approaches, advancing our understanding of Blastocystis, and driving future efforts to translate these findings into improved public health strategies.